Analisis Kebutuhan Material Fiberglass pada Pembangunan Kapal Perikanan Type Longline Berbahan Fiberglass pada Dinas Perikanan Kabupaten Buton Selatan - Samaluddin Samaluddin; La Ode Abdul Gamsir; Dedi Ashari; Rahmawati Djunuda (Pusat riset dan Inovasi Nasional, 2025)
Fiberglass is a composite material composed of a mixture of various chemical substances that react and harden over a specific period of time. The use of fiberglass material composition in the construction of fishing vessels provides durability as a composite material and also influences the overall cost of building fiberglass boats. Construction costs vary significantly depending on the type of vessel, its size, the technology used, and the location of construction. The objective of this study is to determine the volume of fiberglass material used in the construction of fishing vessels. Data collection techniques included observation, interviews, and documentation, followed by a literature review related to the calculation of fiberglass material usage in boat construction with fiberglass structure. This research employs a quantitative descriptive method, which describes the subject under study based on actual conditions and draws conclusions from observed phenomena using numerical statistics. Based on the research findings, it was determined that the construction of one (1) unit of fiberglass fishing vessel requires the following materials: Chopped Strand Mat 300 (CSM 300) amounting to 101.53 kg, Chopped Strand Mat 450 (CSM 450) amounting to 130.352 kg, Woven Roving 600 (WR 600) amounting to 116.130 kg, Resin amounting to 657.171 kg, and Catalyst amounting to 6.969 kg.